(untitled) (Bangladesh Journal of Medical Science, 2013)
Objective: Leishmaniasis is a parasitic disease causing major public health problem in form of visceral and cutaneous types. The cutanoue leishmaniasis is caused by L. tropica, in low-land areas without reservoir; Arthroponatic leishmaniasis (ACL), Zoonotic Cutaneous Leishmaniasis ( ZCL), in high-land. This case report involved; 25 years old Egyptian active young single male adult, stayed in Utama (75 Km far from El-Madina Manowra on the road to Makkah). He presented with three skin lesions on his arms occurred within the last 1-3 months. on examination revealed; volcano- like indurated ulcers which clinically suspected as leishmania lesions . Materials and Methods: Laboratory investigations were involved; skin smear using Giemsa stain, Leishmanin test (LST), polymerase chain reaction (PCR), sequencing and phylogenitic analysis BLAST (NCBI). Results: Microscopy positive LDB (leishmanin donovani bodies), Leishmanin test (LST) was negative. PCR positive L. major . Sequence alignment were 100% with nine Iranian isolates and one Tunisian isolate. After one month of treatment with Pentostam (Sodium stibogluconate) local injections at the site of lesions the lesion progressed from ulcer to scar. Conclusion: L. major is a major species causing cutaneous leishmaniasis in Al-Medina Manowra region in Saudi Arabia. The usage of the polymerase chain reaction (PCR) is a useful diagnostic tool and help to identify the causative species. Bangladesh Journal of Medical Science Vol. 12 No. 03 July 13 Page 325-330 DOI: http://dx.doi.org/10.3329/bjms.v12i3.13189